Distal pancreatectomy with celiac axis resection for locally advanced pancreatic carcinoma: case report - Zanatto, Renato Morato; Beato, Patrícia Medeiros Milhomem; Vieira, Maurício José; Passeri, Celso Roberto (Brazilian Journal of Oncology, 2021)
Long-term survival of pancreatic ductal adenocarcinoma after surgery is still rare. One of the main reasons for unresectability is the tumor invasion of the main vessels, such as the celiac axis, common hepatic artery and superior mesenteric artery. The optimal management of these patients is controversial. Despite the challenges on the topic, we present a case of pancreatic ductal adenocarcinoma with invasion of the celiac axis treated with pancreatectomy and vascular resection plus perioperative chemoradiotherapy. After 30 months of follow-up, hepatic and peritoneal recurrence were identified. Palliative chemotherapy was administered until disease progression and death in March 2020. Surgical resection when used in selected patients, proved to be feasible with acceptable morbidity. Besides that, the aggressive surgical approach associated with multimodal schemes provided an improvement in disease-free and overall survival.
Keywords: Neoadjuvant therapy; Pancreatic neoplasms; Surgery.